Vibration analysis of vehicle engine mounting - Teh, Swee Ing (2013)
Engine mounting is one of the important components in a vehicle to isolate noise and vibration generated by the engine from the driver and passenger. There are three main types of engine mounting such as passive engine mounting, semi-active engine mounting and active engine mounting. The price of the mounting in the market range from the cheapest which is passive engine mounting to the most expensive type of engine mounting which is the active engine mounting. The effectiveness of the engine mounting vary with the price of the engine mounting with the passive engine mounting being the low quality isolation of noise, vibration and harshness (NVH) and the active engine mounting being the highest quality isolation of NVH. In order to reduce the vibrations, noise and harshness (NVH) level for vehicles, understanding about the vibration characteristics of the passive engine mounting in detail is crucial. The objective of this project is to analyze the vibration cause by the engine of a Perodua Kenari on the engine mounting system at different engine revolutions per minute (rpm). The experiment is carried out on a stationary vehicle using DasyLab software. Here, analysis on the vibration obtained from the experiment carried out helps to determine the time response and frequency response of the engine at different rpm. From the results obtained, we can understand the characteristics of the passive engine mounting which is the fundamental of engine mounting among the three types. By understanding the characteristics of the passive engine mounting, improvement can be made on the engine mounting in a low cost method to further improve on the NVH isolation quality